Ahead of others in the authorship order: names with middle initials appear earlier in author lists of academic articles in psychology - Igou, Eric R.; van Tilburg, Wijnand A. P. (Frontiers in Psychology, 2015)
Middle name initials are often used by people in contexts where intellectual performance matters. Given this association, middle initials in people’s names indicate intellectual capacity and performance (Van Tilburg and Igou, 2014). In the current research, we examined whether middle initials are associated with a typical academic indicator of intellectual performance: authorship order of journal articles. In psychology, authorship early in the author list of an article should correspond with greater contribution to this intellectual endeavor compared to authorship appearing later in the author list. Given that middle initials indicate intellectual capacity and performance, we investigated whether there would be a positive relationship between middle initials in author names and early (vs. late) appearance of names in author lists of academic journal articles in psychology. In two studies, we examined the relationship between amount of authors’ middle initials and authorship order. Study 1 used a sample of 678 articles from social psychology journals published in the years 2006 and 2007. Study 2 used a sample of 696 articles from journals of multiple sub-disciplines in psychology published in the years from 1970 to 2013. Middle initials in author names were overrepresented early (vs. late) in author lists. We discuss implications of our findings for academic decisions on authorship orders, potential avenues of further investigation, and applications.